Serum Heavy Metals Level and OS among e-ic Waste Exposed - Zainab Abood Sadoon; Sabah Hussein Enayah (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study is performed in Thi-Qar Province which included a collection of whole blood samplesfrom e-ic repair workers. The survey questionnaire was used which is a standardized tool for this researchand provides for grouping and processing of data and used standardized research instruments such asquestionnaires and interviews of a larger group of subjects to get a clearer and richer examination of the datanecessary for further analysis. A total of 100 whole blood samples were taken with different ages rangedfrom 16 years up to 56 years. Other study groups were 30 subjects from non-e-waste workers. Daily worktime approximately about 6-8 hours for 1 year up to 30 years. The results showed that the percentage ofdiabetic patients among the e-waste population is only (6.5%) all of the diabetes cases were arise for workerswhose exposure exceeded 10 years. The heavy metals concentrations in the serum were measured by usingatomic absorption spectrophotometry and the levels of (Pb) were unexpected, the mean serum Pb levels(24±54 ?g/L) of non-e-waste workers was near to that of e-waste workers (24.6±34 ?g/L) at (p? 0.05),Cd results reported high concentrations in the serum workers of e-waste (35.4±53 ?g/l) compared withworkers as non-e-waste (9.3±17.2?g/l) at (p?0.05). The results of selenium showed an increase in serum Selevels in both groups, (209.4±195.5 ????????/????) for the exposed workers compares with (178.2±29.5 ????????/????) forunexposed workers. The other important aspect on which the study focused is the SOD1/catalase antioxidantsystem. As the study showed a decrease in SOD1 (15.2±2.8????????/????????) in workers of e-waste proportion incomparison to the comparison group (36.8±60????????/????????) at (p=? 0.05). Also, the catalase concentration waslower in e-waste workers (23.9±8ng/ml) more than (28.8±6????????/????????) at (p? 0.05) in non-e-waste workers.